Placental Morphology of Pregnant Iraqi Women with Rheumatic Heart Disease - Al-Assa, Anwar IS; Al-Rubai, Ragwa HI; Al-Ani, Imad M; Al-Ubeidie, Salim R; Al-Kaisy, Kawkab SN; Faisal, Ghasak G (Makara Journal of Health Research, 2016)
Background: Placental morphology and cellular arrangement can be altered in maternal diseases. Rheumatic heart disease (RHD) is a chronic heart condition that can lead to death in pregnant women. The aim of this study is to determine the histological changes of the placenta in pregnant women suffering from RHD. Methods: Placentae were collected from 10 healthy pregnant women, and 31 pregnant women with heart conditions (26 with RHD and 5 with NRHD) who had been admitted to the Baghdad Teaching Hospital. Placental tissues were fixed in 10% formal-saline and were processed for light microscopy. Measurements including the placental weight and diameter of the chorionic villi capillaries were recorded. Results: The results indicate that there are many histological changes in pregnant women with RHD such as hyalinisation, fibrosis of the chorionic villi, proliferation of trophoblastic cells, and thickening of its membrane. Additionally, expectant mothers with RHD experience a reduction in capillary diameter and thickening of the capillary walls, and decreased size and weight of their placenta when compared with the control. Conclusions: Heart diseases, especially RHD, are associated with developmental damage of the placenta in pregnant women by injuring the endothelial cells of the placentas capillaries.